Neuroinvasive West Nile Infection with an Unusual Clinical Presentation: A Single-Center Case Series - Nadia Castaldo; Elena Graziano; Maddalena Peghin; Tolinda Gallo; Pierlanfranco D’Agaro; Assunta Sartor; Tiziana Bove; Roberto Cocconi; Giovanni Merlino; Matteo Bassetti (Tropical Medicine and Infectious Disease, 2020)
The 2018 West Nile Virus (WNV) season in Europe was characterized by an extremely high infection rate and an exceptionally higher burden when compared to previous seasons. Overall, there was a 10.9-fold increase in incidence in Italy, with 577 human cases, 230 WNV neuroinvasive diseases (WNNV) and 42 WNV-attributed deaths. Methods: in this paper we retrospectively reported the neurological presentation of 7 patients admitted to University Hospital of Udine with a diagnosis of WNNV, especially focusing on two patients who presented with atypical severe brain stem involvement. Conclusions: the atypical features of some of these forms highlight the necessity to stay vigilant and suspect the diagnosis when confronted with neurological symptoms. We strongly encourage clinicians to consider WNNV in patients presenting with unexplained neurological symptoms in mild climate-areas at risk.